2005
DOI: 10.1295/polymj.37.355
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Polybinaphthyls Incorporating Chiral (R) or (S)-2,2′-Binaphthyl Entities by Heck Reaction

Abstract: ABSTRACT:Four chiral conjugated polymer-1 (P-1), polymer-2 (P-2), polymer-3 (P-3) and polymer-4 (P-4) were obtained by the polymerization of (S)-6,60 -dibromo-2,2 0 -bisbutoxy-1,1 0 -binaphthyl ((S)-M-1) and (R)-6,6 0 -dibromo-2,2 0 -bisbutoxy-1,1 0 -binaphthyl ((R)-M-1) with 1,4-divinyl-2,5-dibutoxybenzene (M-2) and 1,3,4-oxadiazole-2,5- 1-4 (R) or (S)-1,1 0 -binaphthol (BINOL) have often been used as the starting materials for obtaining chiral binaphthyl compounds. The 2,2 0 -hydroxyl groups of BINOL can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Pu synthesized a series of chiral conjugated polymers incorporating polybinaphthyls into the main chain and compared their UV absorption wavelengths of the polymers with their corresponding repeating units, and found that there is almost no extended conjugation across the 1,1 0 -bond of the binaphthyl units in the backbone of polybinaphthyl [9,40,41]. In this paper, a large red-shift in the electronic absorptions of the conjugated polymers can be attributed to the effective pep* conjugated segment of the linker conjugated unit M-1 and naphthyl group in the repeating unit of polybinaphthyls' main chain [14,15,42,43].…”
Section: Optical Propertiesmentioning
confidence: 71%
See 2 more Smart Citations
“…Pu synthesized a series of chiral conjugated polymers incorporating polybinaphthyls into the main chain and compared their UV absorption wavelengths of the polymers with their corresponding repeating units, and found that there is almost no extended conjugation across the 1,1 0 -bond of the binaphthyl units in the backbone of polybinaphthyl [9,40,41]. In this paper, a large red-shift in the electronic absorptions of the conjugated polymers can be attributed to the effective pep* conjugated segment of the linker conjugated unit M-1 and naphthyl group in the repeating unit of polybinaphthyls' main chain [14,15,42,43].…”
Section: Optical Propertiesmentioning
confidence: 71%
“…The [14,15] and that of the chiral center units (R)-and (S)-2,2 0 -bisbutoxy-1,1 0 -binaphthyl are þ57.8 and À57.2, but [a] D 25 of their conjugated polymers P-1, P-2, P-3 and P-4 are À788, þ822, À165 and þ148, respectively. The absolute values of the special rotation ([a] D 25 ) of the four polymers are larger than their corresponding monomers and the chiral center units (R)-or (S)-2,2 0 -bisbutoxy-1,1 0 -binaphthyl.…”
Section: Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 Compared to the Wittig method, the Pd-catalyzed Heck polycondensation is relatively mild and gives an easy access to various monomers in the preparation of functionalized PPV. 10,27,[43][44][45] In this paper, a typical Heck reaction condition was applied to the polymerization. The C-C cross coupling process was easily carried out in DMF in the presence of a catalytic amount (5 mol%) of Pd(OAc) 2 with Et 3 N and triphenylphosphine (PPh 3 ) under a N 2 atmosphere.…”
Section: Syntheses and Features Of P-1 P-2 And P-3mentioning
confidence: 99%
“…The reported chiral conjugated polymers can be divided into two groups: (1) Main chain chiral conjugated polymers, mainly conjugated polymers containing chiral binaphthylene moieties [9][10][11][12][13][14];…”
mentioning
confidence: 99%